1989
DOI: 10.1093/ajcn/50.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of body composition from bioelectric impedance of body segments

Abstract: The hypothesis that body composition can be estimated accurately from measurements of the length and resistance of the body segments was tested. Weight; stature; whole-body resistance; and the resistances, lengths, and circumferences of the leg, trunk, and arm were measured for 135 white men and women aged 18-58 y. Fat-free mass (FFM) and percent body fat (%BF) were obtained from densitometry. The resistance of the whole body was determined almost entirely by the resistances of the arm and the leg. The accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
102
1
4

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(121 citation statements)
references
References 15 publications
14
102
1
4
Order By: Relevance
“…However, the human body is not an ohmic conductor, mainly because it is anisotropic, ie it cannot be transversed by a constant current density (Baumgartner et al, 1989). Moreover, as far as volume is concerned, the body is better approximated by five cylinders (two for the arms, one for the trunk and two for the legs) than by a single cylinder (Kushner, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the human body is not an ohmic conductor, mainly because it is anisotropic, ie it cannot be transversed by a constant current density (Baumgartner et al, 1989). Moreover, as far as volume is concerned, the body is better approximated by five cylinders (two for the arms, one for the trunk and two for the legs) than by a single cylinder (Kushner, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as far as volume is concerned, the body is better approximated by five cylinders (two for the arms, one for the trunk and two for the legs) than by a single cylinder (Kushner, 1992). Because R is inversely related to S, arms and legs contribute more than trunk to whole-body R (Baumgartner et al, 1989). This has led to the suggestion that segmental RI (obtained by dividing the squared L of a segment by its resistance) may be more appropriate than whole-body RI to predict body composition (Baumgartner et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The subject needs to lay supine, which limits the practical application of the method, especially in the field. Some authors have shown that segmental impedance measurements of the legs or the arms allow fairly accurate estimations of body composition (Baumgartner et al, 1989;Fuller & Elia, 1989;Stewart et al, 1993). More recently, impedance analysers were developed that measure segmental impedance from foot to foot (Nunez et al, 1997;Bell et al, 1998;Jebb et al, 2000) or from hand to hand (Deurenberg et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the algorithms used by these commercially available machines should be revalidated when applied in a population that differs from the one in which they were developed (Heymsfield et al, 1996). Population-relevant equations are recommended to minimise the possible sources of error such as extracellular water volume, hydration status, geometric body shape and adipose volume (Baumgartner et al, 1989;NIH Technology Assessment Conference Statement, 1994). Foot-to-foot BIA has been investigated in several studies, principally in children, healthy adults or in overweight or obese subjects (Hainer et al, 1995;Nunez et al, 1997;Bell et al, 1998;Xie et al, 1999;Jartti et al, 2000;Jebb et al, 2000;Abbott & Davies, 2001;Cable et al, 2001;Powell et al, 2001;Tyrrell et al, 2001;Utter et al, 2001;Batterham et al, 2002).…”
Section: Introductionmentioning
confidence: 99%